PENGARUH TERAPI BERMAIN : BIBLIOTERAPI TERHADAP PENURUNAN RESPON MALADAPTIF PADA ANAK USIA PRASEKOLAH SETELAH DIPASANG INFUS - Yudianto, Andi; Fitriyah, Lailatul (Eduhealth, 2010)
AbstractInvasive procedure : Infuse mointing is one of medical procedure that make trouble to preschool patient. It needs specific communication so they can give adaptive coping to nursing care. The obyective of study was to analyze the effect of bibliotherapy to maladactive response decrease for preschool after infuse lighted. The research uses Quasy Experiment Pretest-Post test Control Group Design , the population is preschool patient that have been infuse mointed in child department RSD Jombang, the sample is 20 respondent by using purposive sampling. We gathered the data by observation method and then we tabulated using distribution frequency and we use T-test with mean level Î± 0,05. After giving bibliotherapie by using T-test we get Ï = 0,04 with mean level Î± 0,05 that mean playing therapy (bibliotherapy) is influence to make maladaptive response decrease for preschool kids after infuse mointing. This Result showed Bibliotherapy is communication technique and also playing theraphy that can help kids to adapt with the environment so maladaptive response kids will less and their anxiety is decrease.Keyword : bibliotherapy, maladaptive response, preschool kids, infuse